2008
DOI: 10.1113/jphysiol.2008.156729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optic nerve injury, glaucoma, and neuroprotection on the survival, structure, and function of ganglion cells in the mammalian retina

Abstract: Glaucoma is an optic neuropathy that originates with pressure-induced damage to the optic nerve. This results in the retrograde degeneration of ganglion cells in the retina, and a progressive loss of vision. Over the past several years, a number of studies have described the structural and functional changes that characterize ganglion cell degeneration in the glaucomatous eye, and following optic nerve injury. In addition, a variety of different strategies for providing neuroprotection to the injured retina ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 40 publications
2
59
1
1
Order By: Relevance
“…[13][14][15][16] Kinetic analysis has shown that Thy-1 mRNA and proteins are gradually lost over the first 2 weeks following optic nerve crush. 17 RGC death follows around 1 to 2 weeks after Thy-1 loss.…”
mentioning
confidence: 99%
“…[13][14][15][16] Kinetic analysis has shown that Thy-1 mRNA and proteins are gradually lost over the first 2 weeks following optic nerve crush. 17 RGC death follows around 1 to 2 weeks after Thy-1 loss.…”
mentioning
confidence: 99%
“…We raise the hypothesis that ocular hypertension acts as an upstream activator of p38 MAPK; this may contribute to induce retinal dysfunction and degeneration. BDNF has been demonstrated to be a potent growth factor that is beneficial in neurodegenerative diseases with synaptic dysfunction [29], in RGC functions following optic nerve injury and diseases [10,11] and in murine models of glaucoma [18,19]. We should take into account the possibility that BDNF reduces retinal dysfunction in DBA/2J mice with elevated IOP [19] by attenuating p38 MAPK phosphorylation, similarly to what was previously reported for amyloid toxicity [29].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is a neurotrophic factor indispensable for the survival and plasticity of several subtypes of neurons in the nervous system, including RGC [9][10][11]. BDNF is locally produced by cells in the ganglion cell and inner nuclear layers [12]; its TrkB receptor is expressed in RGCs, amacrine and Müller cells [13] that represent the cellular target of BDNF trophic action.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotrophins BDNF, NGF, and neurotrophin 4 (NT-4) have neuroprotective effects on retinal ganglion cells compromised by experimentally induced glaucoma or intraorbital optic nerve crush (Parrilla-Reverter et al 2009 ;Colafrancesco et al 2011 ); reviewed in Johnson et al ( 2009 ) andWeber et al ( 2008 ). BDNF and NT-4 preferentially bind TrkB, whereas NGF preferentially binds the related receptor, TrkA, and as mentioned above, LINGO-1 is co-expressed with TrkB, whereas TrkA-mediated signaling stimulates the expression of LINGO-1 Fu et al 2009 ;Skaper 2012a ).…”
Section: Diseasesmentioning
confidence: 96%